Synthesis, Characterization and Spectral Studies of Noble Heterobinuclear Complexes of Transition Metal Ions and their Biological Activity - Netra Pal Singh; Abhay Nanda Srivastava (E-Journal of Chemistry)
Some noble heterobinuclear complexes of transition metal ions with bis(salicylaldehyde)malonyl-dihydrazone in the presence of 5-nitroindazole Cu(II) / Ni(II)- chloride of the type [ML1M‘L2Cl2] or [ML1FeL2Cl2]Cl, where M = Ni(II), Cu(II) and M' = Mn(II), Co(II), have been prepared. All the complexes have been characterized by IR, UV vis and EPR spectroscopy, elemental analysis, magnetic moment and molar conductance measurement. Spectral studies and magnetic moment measurement in DMF suggest the covalent nature of the complexes, except the [ML1FeL2Cl2]Cl complex which is 1:1 electrolyte. An octahedral geometry is proposed for M‘ and square planer for M for the heterobinuclear complexes. The low value of magnetic moment and overlapping EPR signals are due to spin crossover since both of the metals have unpaired electrons with same molecular symmetry. The lowering of the magnetic moment has been discussed. The biological activity (antifungal and antibacterial) of the represented compounds has been studied.